Anti-cholinesterase hybrids as multi-target-directed ligands against Alzheimer's disease (1998–2018). Issue 6 (15th March 2019) - Mishra, Pankaj; Kumar, Amit; Panda, Gautam
Graphical abstract: The medicinal chemistry and pharmacological properties of the lead molecules of 92 hybrids published since 1998-Dec 2017 have been reviewed. Abstract: Alzheimer's disease (AD) is a genetically complex, progressive and irreversible neurodegenerative disorder of the brain which involves multiple associated etiological targets. The complex pathogenesis of AD gave rise to multi-target-directed ligands (MTDLs) principle to combat this dreaded disease. Within this approach, the design and synthesis of hybrids prevailed greatly because of their capability to simultaneously target the intertwined pathogenesis components of the disease. The hybrids include pharmacophoric hybridization of two or more established chemical scaffolds endowed with the desired pharmacological properties into a single moiety. In AD, the primary foundation of medication therapy and drug design strategies includes the inhibition of cholinesterase (ChE) enzymes. Hence the development of ChE inhibition based hybrids is the central choice of AD medicinal chemistry research. To illustrate the progress of ChE inhibition based hybrids and novel targets, we reviewed the medicinal chemistry and pharmacological properties of the multi-target molecules published since 1998-December 2018. We hope that this article will allow the readers to easily follow the evolution of this prominent medicinal chemistry approach to develop a more efficient inhibitor.